1990
DOI: 10.1152/ajprenal.1990.258.6.f1561
|View full text |Cite
|
Sign up to set email alerts
|

AVP reduces transepithelial resistance across IMCD cell monolayers

Abstract: The inner medullary collecting duct (IMCD) is an important site of action for arginine vasopressin (AVP). To examine the mode of action of AVP in this segment, we measured the change in transepithelial resistance of cultured rat IMCD cells grown to confluence on collagen-coated Millicell culture plate inserts in response to AVP. Resistance was measured by use of an EVOM voltage-ohm meter. AVP at 10(-11)-10(-8) M caused a fall in resistance of 6.9 +/- 1.3 to 14.0 +/- 1.4 omega.cm2 (P less than 0.05 to less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The most widely used system for measuring TEER in vitro is the commercially available TransWell culture environment and the “chopstick-style” recording electrode 35,36. For more reproducible and stable TEER measures of leaky cell barriers with lower TEER values, improved recording chambers with embedded electrodes have been constructed.…”
Section: Resultsmentioning
confidence: 99%
“…The most widely used system for measuring TEER in vitro is the commercially available TransWell culture environment and the “chopstick-style” recording electrode 35,36. For more reproducible and stable TEER measures of leaky cell barriers with lower TEER values, improved recording chambers with embedded electrodes have been constructed.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies over several decades have identified a number of cellular level processes that are regulated in response to vasopressin in collecting duct cells (Table 1) (Ganote et al, 1968;Kirk et al, 1984;Star et al, 1988;Mishler et al, 1990;Champigneulle et al, 1993;Nielsen et al, , 1995Simon et al, 1993;Naruse et al, 1995;Sabolić et al, 1995;Chou et al, 2000Chou et al, , 2004Chou et al, , 2008Tamma et al, 2001;Brown, 2003;Yamaguchi et al, 2003;Nunes et al, 2008;Hasler et al, 2009;Nedvetsky et al, 2010; This article has not been copyedited and formatted. The final version may differ from this version.…”
Section: Cellular Physiology Of Aqp2-expressing Renal Collecting mentioning
confidence: 99%
“…When the barrier is established, the cell layer constitutes the electrical resistance between the area beyond the cells and the cell-populated area [24, 25, 26]. This technique has a very high sensitivity for detecting damage of the barrier function, and changes in barrier function can be studied over time [27, 28, 29, 30]. Using this sensitive method, we reported effects of isopropyl unoprostone ophthalmic solution on cultured rabbit corneal epithelial cells [20]and Kawazu et al [19]reported permeation of a β-adrenergic antagonist crossing cultured rabbit corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%